2016
DOI: 10.1071/rd14513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ovarian hormones on the healthy equine uterus: a global gene expression analysis

Abstract: The physiological changes associated with the varying hormonal environment throughout the oestrous cycle are linked to the different functions the uterus needs to fulfil. The aim of the present study was to generate global gene expression profiles for the equine uterus during oestrus and Day 5 of dioestrus. To achieve this, samples were collected from five horses during oestrus (follicle >35 mm in diameter) and dioestrus (5 days after ovulation) and analysed using high-throughput RNA sequencing techniques (RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…These data are detailed in Table 1 and processed using the same pipeline as our generated data, as described subsequently. Publications from these data include Coleman et al 2013, Fushan et al 2015, Marth et al 2015, Mansour et al 2017, Burns et al 2018, and Janecka et al 2018.…”
Section: Sequence Read Archivementioning
confidence: 99%
“…These data are detailed in Table 1 and processed using the same pipeline as our generated data, as described subsequently. Publications from these data include Coleman et al 2013, Fushan et al 2015, Marth et al 2015, Mansour et al 2017, Burns et al 2018, and Janecka et al 2018.…”
Section: Sequence Read Archivementioning
confidence: 99%
“…Due to the increased chance of contamination during oestrus, it is expected that the equine endometrium exhibits a more efficient immune defence response. In fact, Marth et al () reported upregulation of genes involved in the endometrial immune response of mares during oestrus.…”
Section: Introductionmentioning
confidence: 99%
“…A previous next-generation sequencing study found that several pathways related to the immune response were enriched in the oestrus gene expression profiles of cycling mares when compared to their dioestrus profiles, suggesting increased immunological vigilance during oestrus [16]. Inoculation of E. coli into the uterus of healthy mares during oestrus [7] results in a much less pronounced inflammation than in dioestrus [17], in which purulent or serohaemorrhagic vaginal discharge, heavy bacterial growth and acute systemic inflammation were detected.…”
Section: Introductionmentioning
confidence: 99%